Pathways: Examining Street Network Configurations, Structural Characteristics and Spatial Crime Patterns in Street Segments - Kim, Young-An (Journal of quantitative criminology, 2020)
Although theories suggest that street network configurations (pathways) are important factors for understanding the spatial patterns of crime, relatively less attention has been paid to the association between the physical configuration of the street network and the level of crime in place. Consequently, we employed the concept of betweenness centrality in the context of the street network to empirically measure the potential foot traffic passing through a given street segment.